2007
DOI: 10.1080/13575270701353564
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for the Development of Communicative Competence for Children in an Orphanage in South Africa

Abstract: Orphanage life places children at risk of developmental delay, particularly with regard to speech and language acquisition. The aim of this study was to evaluate opportunities for children in an orphanage in South Africa to acquire communicative competence, by examining adultÁchild and childÁchild interactions and by evaluating the structure and resources of the environment. To meet this aim, the researchers familiarized themselves with the structure and daily functioning of the orphanage, and observed and vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 45 publications
2
22
0
1
Order By: Relevance
“…Early institutionalized children reported more depressive symptoms, more aggressive behavior and more internalizing and externalizing problems at primary school age. These findings are in accord with research from other countries (Johnson et al., ; Levin & Haines, ; McCall, ) stating that early institutionalized children are highly burdened.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Early institutionalized children reported more depressive symptoms, more aggressive behavior and more internalizing and externalizing problems at primary school age. These findings are in accord with research from other countries (Johnson et al., ; Levin & Haines, ; McCall, ) stating that early institutionalized children are highly burdened.…”
Section: Discussionsupporting
confidence: 91%
“…Research has shown that institutional care can lead to developmental delay and mental health problems in children (Hermenau et al., ; Johnson et al., ; Levin & Haines, ; St. Petersburg–USA Orphanage Research Team, ). To fill the gap in research concerning consequences of institutional care in Sub‐Saharan African countries, we compared early and late institutionalized Tanzanian children regarding adverse childhood experiences over their entire lifetimes in the family of origin and in institutional care and mental health at primary school age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levin and Haines (2007) examined the language input to children in a multilingual orphanage in Johannesburg, South Africa. In contrast to parental input in traditional settings in the region, as examined in the studies of language socialisation referenced above, paid caregivers in the orphanage did not initiate or respond verbally to children except occasionally to use a child's name or give an instruction, and they did not respond verbally to children's vocalisations.…”
Section: Rehabilitation and Special Education Settingsmentioning
confidence: 99%
“…Many children, who are affected by HIV or AIDS, either themselves or through the loss of parents, are also in need of intervention. Levin and Haines ( 2007 ) examined the language input to children in a multilingual orphanage in Johannesburg, South Africa. In contrast to parental input in traditional settings in the region, as examined in the studies of language socialization referenced above, paid caregivers in the orphanage did not initiate or respond verbally to children except occasionally to use a child's name or give an instruction, and they did not respond verbally to children's vocalizations.…”
Section: Rehabilitation and Special Education Settingsmentioning
confidence: 99%